A systematic analysis of hypermucoviscosity and capsule reveals distinct and overlapping genes that impact Klebsiella pneumoniae fitness. - Laura A Mike; Andrew J Stark; Valerie S Forsyth; Jay Vornhagen; Sara N Smith; Michael A Bachman; Harry L T Mobley (PLoS Pathogens)
Hypervirulent K. pneumoniae (hvKp) is a distinct pathotype that causes invasive community-acquired infections in healthy individuals. Hypermucoviscosity (hmv) is a major phenotype associated with hvKp characterized by copious capsule production and poor sedimentation. Dissecting the individual functions of CPS production and hmv in hvKp has been hindered by the conflation of these two properties. Although hmv requires capsular polysaccharide (CPS) biosynthesis, other cellular factors may also be required and some fitness phenotypes ascribed to CPS may be distinctly attributed to hmv. To address this challenge, we systematically identified genes that impact capsule and hmv. We generated a condensed, ordered transposon library in hypervirulent strain KPPR1, then evaluated the CPS production and hmv phenotypes of the 3,733 transposon mutants, representing 72% of all open reading frames in the genome. We employed forward and reverse genetic screens to evaluate effects of novel and known genes on CPS biosynthesis and hmv. These screens expand our understanding of core genes that coordinate CPS biosynthesis and hmv, as well as identify central metabolism genes that distinctly impact CPS biosynthesis or hmv, specifically those related to purine metabolism, pyruvate metabolism and the TCA cycle. Six representative mutants, with varying effect on CPS biosynthesis and hmv, were evaluated for their impact on CPS thickness, serum resistance, host cell association, and fitness in a murine model of disseminating pneumonia. Altogether, these data demonstrate that hmv requires both CPS biosynthesis and other cellular factors, and that hmv and CPS may serve distinct functions during pathogenesis. The integration of hmv and CPS to the metabolic status of the cell suggests that hvKp may require certain nutrients to specifically cause deep tissue infections.